Active role of participants in neuroempowerment training and supportive neurotechnologies: a theoretical-methodological perspective - Vignati, Benedetta; Crivelli, Davide (Frontiers in Psychology, 2025)
This perspective paper examines the relevance and implications of fostering an active role for participants in neuroempowerment and applied healthcare research, particularly within remote, home-based intervention protocols. Anchored in key psychological constructs—self-efficacy, self-determination, and agency—we argue that the intentional engagement of individuals in their own self-care and enhancement processes is critical to both intervention success and the ecological validity of research outcomes. These constructs provide a framework through which participants are not only involved but become co-agents in shaping their health trajectories. Advances in mobile health technologies and wearable neurotechnologies, such as neurofeedback and biofeedback systems, may further enable participants to access real-time insights into their physiological and neurocognitive states. These tools translate internal processes into actionable feedback, supporting self-regulation, sustained motivation, and embodied learning. Such interactive feedback mechanisms may help bridging unconscious or pre-reflective bodily signals with conscious awareness, thus promoting neurocognitive autonomy. We propose that empowerment-based interventions—especially those incorporating wearable systems—should be intentionally designed to reinforce autonomy, competence, and relatedness, fostering engagement and long-term behavioral change. This participatory model moves beyond traditional therapist-centered approaches, emphasizing personalized, scalable, and self-directed care. Additionally, we highlight the need for research methodologies that recognize participants as co-constructors of their own empowerment paths, encouraging future studies to adopt inclusive, action-oriented frameworks. By integrating psychological theory, neuroscientific models, and digital health innovations, this perspective outlines a multidimensional approach to neuroempowerment, aimed at promoting self-awareness, agency, and meaningful transformation in both clinical and non-clinical populations.